Deposits as a stable source of bank funding. Did the global finance crisis influence the banks’ funding structure? - Iwanicz-Drozdowska, Małgorzata; Penczar, Marta; Kujawski, Lech; Liszewska, Monika (Publishing House of Wroclaw University of Economics and Business, 2021)
The paper analyses the bank-specific and macroeconomic factors which determined the share of deposits in the funding structure of 184 EU listed banks in 2004-2016. The findings show that the global financial crisis (GFC) was one of the main factors that influenced the banks’ funding models. The authors document the banks’ return to funding from retail and corporate deposit markets, reducing the diversity in European banking sectors. The paper reports that the set of determinants affecting the banks’ funding policies were different in the GFC in comparison to periods before and after the crisis. The authors concluded that the influence of the net loans to the total deposit ratio on the deposit to total assets ratio was higher in the crisis period. On the other hand, return on assets had a lower negative impact on the banks’ funding model since they were forced to improve their profitability during the GFC.
Argumenta Oeconomica, 2021, Nr 2 (47), s.19-38
Keywords: bank's business models; deposit funding; financial crisis